Efficiency of RNA extraction protocols in different types of coffee plant tissues - Paula, Márcia Fabiana Barbosa de; Ságio, Solange Aparecida; Lazzari, Fabiane; Barreto, Horllys Gomes; Paiva, Luciano Vilela; Chalfun-Junior, Antonio (Coffee Science - ISSN 1984-3909, 2012)
In order to use sensitive techniques of molecular biology, such as the study of differentially expressed genes, a highqualityRNA in suitable quantities is necessary. Due to the presence of several varieties and often expressive quantities of secondarycompounds in plants, there is no standard method for the isolation of nucleic acids that can be used for all species. Polyphenols andpolysaccharides are the compounds that interfere the most in the extraction process, and when they are present, a low-quality RNAis produced. Four RNA extraction methods (CTAB method, Hot Borate, CONCERT and Tri Reagent), in four different coffee tissues(root, leaf, flower and fruit) were tested in this work, aiming at determining which method is more efficient. It was observed that theCTAB and Hot Borate methods, in which PVP and/or -mercaptoethanol were added and precipitation with LiCl was performed,presented more pure RNA, with no degradation observed in any of the tissues, being suitable for further gene expression analysis.High-quality RNA was not obtained from any tissue in the extraction with Tri Reagent, which includes the use of phenol, and thusexpression analysis was disturbed. The CTAB macroextraction method presented samples with the highest RNA quality and largestquantities in all tissues. Future works need to be carried out aiming the standardization of this macroextraction method.